Prevalence of multimorbidity and its associations with hospitalisation or death in Japan 2014–2019: a retrospective cohort study using nationwide medical claims data in the middle-aged generation - Takeo Nakayama; Yoshiyuki Saito; Shingo Fukuma; Ataru Igarashi (BMJ Open)
Objective To describe the prevalence of multimorbidity and its associations with clinical outcomes across age groups.Design Retrospective cohort study using nationwide medical claims data.Setting Carried out in Japan between April 2014 and March 2019.Participants N=246 671 Japanese individuals aged 20–74 enrolled in the health insurance were included into the baseline data set for fiscal year (FY) 2014. Of those, N=181 959 individuals were included into the cohort data set spanning FY2014–FY2018.Exposures Multimorbidity was defined as having ≥2 of 15 chronic conditions according to the International Classification of Diseases 10th Revision codes of the Charlson Comorbidity Index.Primary and secondary outcomes Primary outcome: the standardised prevalence of multimorbidity across age groups was evaluated using data from FY2014 and extrapolated to the Japanese total population. Secondary outcome: hospitalisation or death events were traced by month using medical claims data and insurer enrolment data. Associations between multimorbidity and 5-year hospitalisation and/or death events across age groups were analysed using a Cox regression model.Results The standardised prevalence rate of multimorbidity in the nationwide Japanese total population was estimated to 26.1%. The prevalence rate with age was increased, approximately 5% (ages 20–29), 10% (30–39), 20% (40–49), 30% (50–59), 50% (60–69) and 60% (70–74). Compared with individuals aged 20–39 without multimorbidity, those with multimorbidity had a higher incidence of clinical events in any age group (HR=2.43 (95% CI 2.30 to 2.56) in ages 20–39, HR=2.55 (95% CI 2.47 to 2.63) in ages 40–59 and HR=3.41 (95% CI 3.23 to 3.53) in ages ≥60). The difference in the incidence of clinical events between multimorbidity and no multimorbidity was larger than that between age groups.Conclusions Multimorbidity is already prevalent in the middle-aged generation and is associated with poor clinical outcomes. These findings underscore the significance of multimorbidity and highlight the urgent need for preventive intervention at the public healthcare level.